(untitled) (Journal of Applied Learning and Teaching, 2024)
The impact of artificial intelligence in education has been well documented. However, the sustainability of artificial intelligence-driven classroom assessment has not been the focus of much literature. This study sought to cover this research gap by examining the role of curriculum innovation, quality, and viability when mediated by computer self-efficacy and digital literacy in sustainable AI-driven classroom assessment. A total of 1607 respondents were used for the study. A questionnaire that was validated by experts and the psychometric properties of exploratory and confirmatory factor analysis were used to determine the structure and dimensionality of the scale. The findings of the study revealed that curriculum innovation directly affects curriculum viability, curriculum quality, digital literacy, computer self-efficacy, and sustainable AI-driven classroom assessment. At the same time, curriculum quality and viability also affect digital literacy, computer self-efficacy, and sustainable AI-driven classroom assessment. The mediation of digital literacy and computer self-efficacy in the nexus between curriculum innovation and sustainable AI-driven classroom assessment was significant. However, these mediators were insignificant in the nexus between curriculum quality and sustainable AI-driven classroom assessment. The implications of the findings were discussed, especially for policy developments.